A cost analysis of the treatment of first-line uncomplicated malaria in the Tonga district of Mpumalanga - Wilkins, Justin (Division of Clinical Pharmacology, 2018)
Following the completion of a detailed baseline study of malaria in the region, a model was developed to assess the cost-effectiveness of switching from chloroquine to sulfadoxine-pyrimetharnine as first line treatment in the Tonga district of Mpumalanga, South Africa, where malaria is seasonal and the population is non-immune. In vivo drug resistance was used to create a resistance variable, which was used to assess the 1997 relative costs to the health care system of employing the two drugs, analysing factors such as drug costs, staff time, transport costs, maintenance costs, utility costs, training costs and consumables costs to generate an average cost-effectiveness ratio. The model was subsequently used to estimate the average cost-effectiveness ratios of nine other potential agents for the treatment of first line malaria, including artesunate monotherapy, artesunate combinations, pyronaridine, atovaquone-proguanil, co-artemether, halofantrine, amodiaquine, and mefloquine. It was found that sulfadoxinepyrimethamine was 5 times more cost-effective as first line therapy than chloroquine. Of the other modelled drugs, it was recommended that an artesunate combination should be implemented when it becomes necessary to replace sulfadoxine-pyrimethamine; artesunate-mefloquine and artesunate-SP were estimated to be 6 times and 9 times as cost-effective as chloroquine, respectively.